Participative planning and information flow within management control - Tomasz Dyczkowski; Joanna Dyczkowska (Zeszyty Teoretyczne Rachunkowości, 2016)
The paper examines the relationships between two different approaches to planning processes (participa- tive and non-participative) and information flows within management control in companies. It augments the existing theoretical and empirical research by coupling management control and management infor- mation with participative planning, not only in operational but also in the strategic perspective. The re- sults presented in the paper stem from two consecutive studies, conducted between November 2010 and January 2012 and between November 2013 and January 2014. The studies comprised 397 and 179 Polish companies respectively. The authors formulated two hypotheses linking participative planning with upward and downward management information flows. The paper employed a quantitative approach, using the Spearman rank correlation analysis and hierarchical clustering using the Ward method, which enabled comparative analyses both in reference to various groups of companies included in particular research samples and over time. The results obtained showed the positive influence of participative plan- ning both on upward and downward information flows in enterprises. In particular, participative planning reduced information imbalances between top (the management) and lower (employees of functional departments) tiers in organisation structures.